Upaya Pengentasan Kemiskinan Menuju Pencapaian Tujuan Pembangunan Berkelanjutan (SDGs) di Indonesia - Rahayu, Sri Endang; Febriaty, Hastina (CERED Indonesia, 2025)
This study aims to analyze poverty alleviation efforts in Indonesia in relation to the achievement of the Sustainable Development Goals (SDGs). The research focuses on examining poverty trends, identifying influencing factors, and evaluating government policies related to poverty reduction during the 2004–2023 period. The research uses a quantitative approach with multiple linear regression analysis. The independent variables include the unemployment rate, income inequality (Gini Ratio), and Human Development Index (HDI), while the dependent variable is the poverty rate. The results of the study show that 1) the open unemployment rate (TPT) has a positive and significant effect on the poverty rate in Indonesia, 2) the income inequality rate has a negative and insignificant effect on the poverty rate in Indonesia and 3) the human development index (HDI) has a negative and significant effect on the poverty rate in Indonesia. In addition, Although the overall poverty rate has declined, structural challenges such as inequality and human capital quality remain obstacles. Therefore, strengthening inclusive social policies, improving education and health services, and creating sustainable employment are key strategies to accelerate the achievement of the SDGs in Indonesia. Keyword : Poverty; SDGs; Unemployment; Inequality; HDI